Results of the cementless Plasmacup in revision total hip arthroplasty: a retrospective study of 72 cases with an average follow-up of eight years - Lakemeier, Stefan (BioMed Central, 2010)
BACKGROUND: There are multiple revision implant systems currently available for socket revision in revision total hip arthroplasty. Up until now, not all of these systems have been followed up with regards to their long-term use as a revision implantation. For the first time, this study presents the hemispherical porous-coated socket Plasmacup SC, produced by Aesculap, Tuttlingen, Germany, and the clinical and radiological mid-term results of this revision cup implant. METHODS: Over a period of ten years the Plasmacup SC press-fit-cup was used as a revision implant in 72 consecutive aseptic cases which were included in this retrospective study. The mean follow-up period was 8 years. Bone graft transplantation was performed in 32% of all cases. In 90%, the cup was fixed with additional screws. The follow-up radiographs were analysed with regards to cup migration, osteointegration and osteolysis in the DeLee zones using a computer aided program taking the teardrop figure as a main point of reference. For clinical evaluation the Harris-Hip-Score and the WOMAC-Score were utilized. RESULTS: At the follow up examination, the mean Harris-Hip-Score was 83.5 points and the mean WOMAC-Score 34.7 points. 93% of all patients were satisfied with the result of the operation. No aseptic cup loosening could be observed and only one cup had to be removed due to infection. No significant longitudinal or transversal cup migration could be observed. CONCLUSION: Aesculap's Plasmacup SC is suitable as a cementless cup revision implant. There is stable cup osteointegration, post press-fit implantation, even in the case of major acetabular bone defects.